Influence of The Liveworksheet Assisted Problem-Based Learning Model on Students' Mathematical Literacy Ability - Asma Ul Husna; Meyta Dwi Kurniasih (Universitas Wiralodra, 2023)
Mathematical literacy ability is a person's ability to understand mathematical problems that exist in everyday life. This study aims to describe the effect of the LiveWorksheet-assisted problem based learning (PBL) model on students' mathematical literacy abilities in Trigonometry material. The sample of this study were 2 classes with a total of 64 high school students in class X. This quantitative research method used data analysis techniques with the 3-test which had previously passed the analysis prerequisite tests, namely the normality test and homogeneity test. The results showed that the effect of the LKS-assisted PBL model had an effect on the mathematical literacy skills of class X students. This was indicated by the average problem-based learning model assisted by LKS obtaining an average value of 89.125 and the control class obtaining an average value of 83.218 so that it has a difference of 5.907 . Thus, it can be said that the class that applies the LKS-assisted problem-based learning model obtains a greater average score. , so this causes to be rejected at a significance level of 0.05 and degrees of freedom , then there is an effect of the PBL Model Liveworksheet on students' mathematical literacy abilities.